The "little emperor" and the luxury brand: How overt and covert narcissism affect brand loyalty and proneness to buy counterfeits. Issue 7 (29th April 2018) - Fastoso, Fernando; Bartikowski, Boris; Wang, Siqi
Abstract: The authors build on approach‐avoidance motivations theory to investigate the relationship between narcissism and luxury brand consumption. Narcissistic consumers, that is, those showing excessive conceit, are prone to consuming high‐prestige products and are thus attractive targets for luxury brands. Yet despite research in psychology distinguishing two types of narcissism, overt (or grandiose) and covert (or vulnerable) narcissism, little is known about how luxury consumption varies by these forms of narcissism. This paper focuses on Chinese Generation Y consumers to examine how overt and covert narcissism differ in their effects on luxury brand loyalty and proneness to purchase counterfeits as well as the moderating role of brand‐image self‐image congruity on the relationship between overt/covert narcissism and brand loyalty. Findings highlight the need for marketers to understand narcissistic targets more clearly in order to develop successful strategies to foster brand loyalty and diminish counterfeit consumption.